Role of the Tree Species Selected in Developing Swampy Forest System for Passive Treatment of Acid Mine Drainage - Noor, Ihsan; Arifin, Yudi Firmanul; Priatmadi, Bambang Joko; Saidy, Akhmad Rizally; Mansur, Irdika (Technium Sustainability, 2022)
Coal mining is one of economic sector that requires forestry area in Indonesia. Most of coal mining concession are forestry area loan use from the government and during mining operation facing with acid mine drainage (AMD). AMD passive treatment can be integrated with revegetation process that related with better handling of overburden (OB) with potential acid forming (PAF) during reclamation processed. The most expensive methods and uncertainty process are the use of quick lime in treatment of AMD. During operation and preparing mine closure stage need to create the effective one to comply with the regulation. “Swampy Forest (SF) system” is an alternative method of sustainable and naturally process. Selecting the appropriate tree species as a preliminary process to develop a better SF system by batch experiment in the form of a forest constructed wetland. The tree species selected are Nauclea orientalis (lonkida tree) and Melaleuca cajuputi (kayuputih tree) as non-local species then Nauclea subdita (bangkal tree) and Melaleuca leucadendron (galam tree) as local species have been selected. Local species higher in Fe and Mn adsorption in pH of AMD <4 then nonlocal species higher in Fe and Mn adsorption on pH of AMD >4 condition.